Development of FeO, TiO2-SiO2-CaCO3 system as a welding flux (2004)
Using local raw materials, various metal-arc welding fluxes were formulated. A ternary system of FeO, TiO2- SiO2-CaCO3 gave satisfactory results. Average values of 546 N/mm2 ultimate tensile strength and 10% elongation were obtained from all-weld metal tensile specimen. The formulation also gave a metal deposition efficiency of 88.9%